El Desarrollo De La Coordinación En Los Fundamentos Técnicos Del Fútbol En La Categoría 10-12 Años. Estudio De Caso: Test De Coordinación En La Escalera - Orlando David Mazón Moreno; Jorge Giovanny Tocto Lobato; Marlon Gabriel Llanga Colcha; Ramón Fernando Bayas Machado; Juan Carlos Bayas Machado (European Scientific Journal, ESJ, 2017)
The aim of this study was to determine the development of coordination and its impact on the technical fundamentals of football in the 10 – 12 years of age category in “Unidad Educativa Liceo Policial Chimborazo” by a guide of exercises in order to improve coordination and soccer technical fundamentals for six weeks. For this research 25 players were evaluated. A pre and post-test were applied for coordination on the stairs. The results acquired in the implementation of the excise guide coordination and technical foundations of football were significant at the time of implementation of the post test. The exercise used in this guide and applied training sessions were coordinating the ball with the food. It has been concluded that coordination affects within the basic foundation of soccer and improve their lifestyle.